3D printing of dental restorations: Mechanical properties of thermoplastic polymer materials. (July 2021) - Schönhoff, Lisa Marie; Mayinger, Felicitas; Eichberger, Marlis; Reznikova, Elena; Stawarczyk, Bogna
Abstract: In the seminal field of 3D printing of dental restorations, the time and cost saving manufacturing of removable and fixed dental prostheses from thermoplastic polymer materials employing fused filament fabrication (FFF) is gaining momentum. As of today, the additive manufacturing of the established semi-crystalline polyetheretherketone (PEEK) requires extensive post-processing and lacks precision. In this context, the amorphous polyphenylene sulfone (PPSU) may provide a higher predictability and reliability of the results. The aim of this study was to investigate the mechanical properties of PPSU and PEEK processed by FFF (PPSU1-3D (PPSU Radel) and PPSU2-3D (Ultrason P 3010 NAT)) or extrusion (PPSU1-EX (Radel R-5000 NT) and PEEK-CG (PEEK Juvora)). Three-point flexural strength, two-body wear, and Martens hardness (HM) and indentation modulus (EIT ) were tested after aging. One-way ANOVA, the Kruskal-Wallis and the Pearson's and Spearman's correlation tests were computed (α = 0.05). PPSU1-3D and PPSU2-3D showed lower flexural strength values than PPSU1-EX and PEEK-CG. PPSU1-3D showed the highest, and PEEK-CG and PPSU1-EX the lowest height loss. The highest HM and EIT results were observed for PEEK-CG and the lowest for PPSU1-3D. Correlations were observed between all parameters except for the application height. In conclusion, the manufacturing process affected the flexural strength of PPSU, with 3D printed specimens presenting lower values than specimens cut from prefabricated molded material. This finding indicates that the 3D printing parameters employed for the additive manufacturing of PPSU specimens in the present investigation require further optimization. For 3D printed specimens, the quality of the filament showed an impact on the mechanical properties, underlining the importance of adhering to high quality standards during filament fabrication. Extruded PPSU led to comparable results with PEEK for flexural strength and two-body wear, indicating this novel dental restorative material to be a suitable alternative to the established PEEK for the manufacturing of both removable and fixed dental prostheses. Graphical abstract: Image 1 Highlights: 3D printing of polyphenylene sulfone led to impaired flexural strength values. The filament quality influenced the mechanical properties of polyphenylene sulfone. Extruded PPSU led to comparable results to the established polyetheretherketone.